Examine the impact of the implementation of an electronic medical record system on operating theatre efficiency at a teaching hospital in Australia - Chuang, Tzu-Yi Arron; Yii, Nathan; Nyandowe, Masimba; Iyer, Ramesh (International Surgery Journal, 2019)
Background: The utilization of electronic medical record (EMR) system has become the mainstay of healthcare system in developed countries. In the last five years, Queensland Health has gradually implemented EMR system for hospitals in Queensland, Australia. As far as we are aware, no study has been conducted to assess the impact of the EMR implementation on operating theatre efficiency in Australia. Methods: A retrospective review of general surgery operating room on time start data was performed for a period of 2 months prior and 2 months following implementation of the EHR. A delay was defined as the time between the scheduled start time and “first in” times. Outcomes measured included the total number of sessions run, number of sessions starting late, average delay time and case cancellations. Results: During the EMR training period, the number of sessions which had delayed increased from 13.2％ to 31.0%. Following implementation of the EMR, delays were present for 88% of sessions for the first month with an average delay time of 21.8 minutes. The second month showed an overall improvement with 69% of sessions delayed and a reduced average delay time of 10.4mins. Conclusions: The implementation of a new electronic medical record system is associated with delays in theatre start times especially during the training period and first month of use. Evidence of recovery of service efficiency however is seen by the second month post-implementation with further expected improvement if trends continue.